Genotyping by PCR and High-Throughput Sequencing of Commercial Probiotic Products Reveals Composition Biases - Morovic, Wesley; Hibberd, Ashley A.; Zabel, Bryan; Barrangou, Rodolphe; Stahl, Buffy (Frontiers in Microbiology, 2016)
Recent advances in microbiome research have brought renewed focus on beneficial bacteria, many of which are available in food and dietary supplements. Although probiotics have historically been defined as microorganisms that convey health benefits when ingested in sufficient viable amounts, this description now includes the stipulation “well defined strains,” encompassing definitive taxonomy for consumer consideration and regulatory oversight. Here, we evaluated 52 commercial dietary supplements covering a range of labeled species, and determined their content using plate counting, targeted genotyping. Additionally, strain identities were assessed using methods recently published by the United States Pharmacopeial Convention. We also determined the relative abundance of individual bacteria by high-throughput sequencing (HTS) of the 16S rRNA sequence using paired-end 2x250bp Illumina MiSeq technology. Using multiple methods, we tested the hypothesis that products do contain the quantitative amount of labeled bacteria, and qualitative list of labeled microbial species. We found that 17 samples (33%) were below label claim for CFU prior to their expiration dates. A multiplexed-PCR scheme showed that only 30/52 (58%) of the products contained a correctly labeled classification, with issues encompassing incorrect taxonomy, missing species and un-labeled species. The HTS revealed that many blended products consisted predominantly of Lactobacillus acidophilus and Bifidobacterium animalis subsp. lactis. These results highlight the need for reliable methods to qualitatively determine the correct taxonomy and quantitatively ascertain the relative amounts of mixed microbial populations in commercial probiotic products.